Cosmological distance scale. Part 17: Coincidence of coincidences - Levin, S. F. (Measurement techniques, 2024)
The article considers an alternative interpretation of data that were used to conclude the accelerated expansion of the universe in 1998–1999. This interpretation was prompted by doubts as to whether the neglect of the local void effect is justified, as well as by several results obtained when solving the measurement problems of cosmology using the specialized programs MCM-stat, MCM-stat M, and MMI-verification. The programs are designed to automate the statistical analysis of data in the verification and calibration of measuring instruments. The first two programs were applied in the structural and parametric identification of isotropic and anisotropic Friedmann-Robertson-Walker models, respectively, in the form of a relationship between the photometric distance and the redshift of Type Ia supernova in the class of power series. This dependence was analyzed as a mathematical model of the redshift cosmological distance scale. As a physical mechanism underlying the massive accelerated movement of galaxy streams, the study adopted the gravitational dipole of inhomogeneity of the large-scale structure of the universe. A dipole of this kind consists of a pair of superclusters and a supervoid on opposite sides of the celestial sphere. The uneven gravitational interaction in such a pair is perceived as an additional repulsive force of an order comparable to the effect of a supercluster. At least five gravitational dipoles of this kind are shown to exist, concentrating in the region of Galactic poles and forming a giant Galactic polar gravitational dipole. The coincidence of the Galactic polar gravitational dipole and the system of giant superclusters of galaxies in the northern Galactic hemisphere and the system of supervoids in the southern Galactic hemisphere is called the coincidence of coincidences; this fact is considered as a hypothesis alternative to the that about the accelerated expansion of the universe. However, in order to explain the observed facts, it is not necessary to introduce the exotic concepts of dark matter and dark energy.